2004
DOI: 10.1074/jbc.m405212200
|View full text |Cite
|
Sign up to set email alerts
|

Human Rad51C Deficiency Destabilizes XRCC3, Impairs Recombination, and Radiosensitizes S/G2-phase Cells

Abstract: The highly conserved Rad51 protein plays an essential role in repairing DNA damage through homologous recombination. In vertebrates, five Rad51 paralogs (Rad51B, Rad51C, Rad51D, XRCC2, and XRCC3) are expressed in mitotically growing cells and are thought to play mediating roles in homologous recombination, although their precise functions remain unclear. Among the five paralogs, Rad51C was found to be a central component present in two complexes, Rad51C-XRCC3 and Rad51B-Rad51C-Rad51D-XRCC2. We have shown previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
54
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 68 publications
16
54
0
1
Order By: Relevance
“…Previous studies also suggest that the stability of other Rad51 paralog proteins is dependent on Rad51C (60). We found that depletion of Rad51C led to a significant reduction in cellular levels of Xrcc3, as was observed previously (60), yet levels of Rad51B, Rad51D, and Xrcc2 remained unaffected (supplemental Fig. 3A).…”
Section: Dna Damage-induced Nuclear Transport Of Rad51 Involves Both supporting
confidence: 88%
“…Previous studies also suggest that the stability of other Rad51 paralog proteins is dependent on Rad51C (60). We found that depletion of Rad51C led to a significant reduction in cellular levels of Xrcc3, as was observed previously (60), yet levels of Rad51B, Rad51D, and Xrcc2 remained unaffected (supplemental Fig. 3A).…”
Section: Dna Damage-induced Nuclear Transport Of Rad51 Involves Both supporting
confidence: 88%
“…Previous studies of mammals suggested that Rad51 paralogs form two complexes, BCDX2 and CX3, both containing Rad51C (Miller et al, 2004). Moreover, Lio et al (2004) reported that inhibition of Rad51C reduced the protein levels of Xrcc3 and Rad51B in four other Rad51 paralogs, although the reduction of Rad51B was less and more transient. Thus, it is thought that Rad51C is a central component of Rad51 paralog complexes and that it may regulate the amount of Rad51 paralog complexes.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, spontaneous sister chromatid exchange (SCE), which is mainly mediated by HR (Sonoda et al , 1999), was similar between WT and SirT7 −/− cells (Appendix Fig S7C–E). We used a HR reporter locus stably integrated in HT1080 cells (Lio et al , 2004). This HR assay is based on the recovery of a puromycin resistance gene after successful repair of an I‐SceI‐induced DSB.…”
Section: Resultsmentioning
confidence: 99%